Filodemo y el pensamiento antropológico griego: Phld. Sto. (PHerc. 155E y 339), col. XXI - García González, Jesús María (Florentia Iliberritana, 2016)
The closing section of the papyrus can be explained otherwise than Dorandi did it. The reference to the γηγϵνϵις and also to non-Greek peoples like the Thyrrenians, Campanians, etc., is an ethno-anthropological topic used for excluding both Diogenes' and Zeno's areskonta from the civilized life of Greeks.